ANALYSIS DECISION SUPPORT SYSTEMS IN ASSISTING THE MARKETING MANAGER AT PT. BORSUMIJ WEHRY INDONESIA THROUGH A PROGRAM MICROSOFT EXEL - Mayu Sofia Mandiri; Aqwam Rosadi Kardian,S.kom.,MMSI (Jurnal Sistem Informasi, 2000)
Company Borsumij Wehry Indonesia is a multi division and geographically dispersed, and vertically integrated as the distribution of canned food. This company is typical of today's companies, namely, that the mobilization of resources as an organization is directed to the various markets for the benefit of shareholders groups. But such cases are not common characteristics of many who owned a large company, which is able to profitably use the information system that processes transactions from 20 different organizations with a system together and then present it to the management company quickly. Will obtain the appropriate level of benefits, in addition to control information to determine the basis for organizational components and compared with the plan. Top management received a brief report that shows the benefits of each organization, based on division and overall by a period and the current year, which compared with the plan. Part responsible for the marketing of income data with data submitted contributions are less direct cost of the standard. As far as the involvement of the marketing department, direct costs of the standard is fixed. Therefore, this part of the answer can not be held accountable in maximizing the contribution by varying the items that were under the control of volume, price, customer and product ingredients. The need for hardware and software continue to increase along with the rapid development of computers today. A sophisticated hardware that will not be useful without supported by software that helps in preparing the report as information for each management through computer programs. On this occasion, the author tries to analyze and design a marketing system on PT. Borsumij Wehry Indonesia. Analysis and design of the system is given a lesson in data processing curriculum.